Profitability of agro-forestry based soil fertility management technologies : The case of small holder food production in Western Kenya - Maithya, JM; Kimenye, L.N.; Mugivane, FI; Ramisch, Joshua J. (Springer, 2007)
Persistent food insecurity accompanied by low and declining farm household incomes are a common feature of many small holder maize and bean producers in western Kenya. This has been largely attributed to soil nutrient depletion, among other factors. One way of addressing soil fertility problems in many maize-based cropping systems is the use of agro-forestry based technologies. We carried out a survey in western Kenya (Vihiga and Siaya districts) aimed at analyzing the financial and social profitability of use of agroforestry based (improved tree fallows) and other soil fertility management technologies among smallholder farmers. The Policy Analysis Matrix (PAM) was used to determine the financial and social profitability of different production systems, which were categorized on the basis of the technology used to address soil fertility. Farm budgets were first prepared and in turn used to construct the PAMs for six production systems namely: maize bean intercrop without any soil fertility management inputs; maize bean intercrop with chemical fertilizers only; maize bean intercrop with a combination of chemical fertilizers and improved fallows; maize bean intercrop with improved fallows only; maize bean intercrop with a combination of improved fallows and rock phosphate; and maize bean intercrop with Farm Yard Manure (FYM) only. Results revealed that use of chemical fertilizers with improved fallows was the most profitable technology and thus the study recommended that farmers be encouraged to intensify the use of chemical fertilizers. To make chemical fertilizers more accessible to farmers, the study also recommended that good linkages be made between farmers and micro credit institutions so that small scale farmers are not actually biased against due to lack of collateral when credit is being advanced to clients.